Propuesta de plan de gestión de proyecto para la implementación del sistema OEE Toolkit en GSK - Chaves-Martínez, Danny (Instituto Tecnológico de Costa Rica, 2016)
GSK Costa Rica is a pharmaceutical company engaged in the manufacture of medicaments for improving prevention and health of people. It is a company focused on its operations, for this reason has no projectized structure. There is a necessity to implement an automated calculation of the overall efficiency of production lines, ensuring that regardless of the level of complexity of the project complies with the scope, time and cost. This project has attempted to develop since 2008, but without a proper management thereof, has been canceled three times, causing loss of money and resources. Because corporate initiative to reactivate the project and Costa Rica been chosen to be the first plant to implement this automated OEE measurement, San Jose site required a management plan for the project to ensure success of the project in time, cost and scope. Therefore, this paper presents a literature review of project management in order to develop a project plan for implementing the OEE Toolkit, based on the actual projects assets that the company has and good practices globally recognized. An applied research was used for this project, it deals with the solution of practical problems in the application of science, using the interview and documental review as the main tools to prepare the project plan. With the GSK Costa Rica assets for project management and supplemented with some tools established on good practices in project management such as ISO 21500, PMBoK® and the methodology established by Brown and Graundy for pharmaceutical industries, the proposed plan concluded that the "OEE Toolkit" will cost 68.839 £ with a 10% of contingency for unforeseen and be operational by June 2016.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2016.
Keywords: Plan; Tiempo; Alcance; Costo; GSK